New species of Mesenopsis Godman & Salvin, 1886 (Lepidoptera: Riodinidae: Symmachiini) from southeastern Brazil, with an illustrated key to the genus - Dias, Fernando Maia Silva; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2013)
A new species, Mesenopsis jordana sp. nov., from southeastern Brazilian states of Minas Gerais, Rio de Janeiro, and São Paulo is described and a taxonomic dichotomous key for species of the genus Mesenopsis is provided. Additionally, mimetic models for species of Mesenopsis are suggested and a new distribution record for M. albivitta is provided.